Food Literacy among Adolescents from public schools in Montes Claros, MG, Brazil, 2019/2020 - Farias, Paula Karoline Soares; Sales, Marinilza Soares Mota; Barbosa, Ana Carolina Mota; Filho, Giovani Siervi Andrade; Leite, Agda Silene; Oliveira, Fabíola Belkiss Santos de; Eleutério, Tatiane Palmeira; Reis, Érika Cardoso dos; Monteiro, Elma Lúcia de Freitas; Souto, Cláudia de Andrade; Santos, Aline Soares Figueiredo; Sampaio, Helena Alves de Carvalho; et al. (International Journal of Advanced Engineering Research and Science, 2022)
Objective: To evaluate adolescents’ food literacy. Methods: The estimated samples were 496 and 497 schoolchildren aged 12 and 15 years old, according to the following parameters: universes 4458 and 4524 respectively; prevalence 50%; confidence level 95% (Z=1.96); sampling error 5%; non response rate 10%, and deff=1.4. By simple random drawing, public schools where there were adolescents of the recommended index ages were included. To assess food literacy, questions that addressed access to information, understanding, evaluation, and application of the information about food were considered. The data were collected by trained academics, who used software developed for this purpose. The descriptive analyses were made using the Statistical Package for the Social Sciences - SPSS, version 25.0. Results: 734 students participated, being 236 aged 12 and 498 aged 15, with response rates of 47.58% and 100%, respectively. It could be observed that, regarding the variable access, 9.3% (n=68) of the schoolchildren reported they had never had access to any information about proper nutrition. The main person / professional who had provided those teenagers with this information was the nurse (91.6% / n= 663), and the radio was the main means (90.2% / n=654). 80.0% of the respondents (n= 585) reported they had had access to the topic "Healthy and unhealthy eating". Most respondents reported difficulties in understanding, evaluation, and application of healthy eating information. Conclusion: Those teenagers’ food literacy was adequate in the access dimension, but there were difficulties in the understanding, evaluation and application of information dimensions. Thus, the need to perform health care in a broader way is confirmed, with interventions that provide effective food literacy for adolescents, culminating in better health outcomes.